ANALYSIS OF NATIONAL RESEARCH ON DECISION-MAKING IN THE PERIOD 2004-2014 - Ramos, Simone Cristina; Takahashi, Adriana Roseli Wünsch; Roglio, Karina De Déa (Contextus - Revista Contemporânea de Economia e Gestão, 2015)
The purpose of this article is to analyze the national publications on organizational decisionmaking process in journals (A1 to B2) and events promoted by ANPAD from 2004 to 2014. The analysis of the 275 articles indicates that the subject has little representation in publications, with an average of two articles in each journal in 11 years. Although involving a large number of authors (n = 556), only 4% has over two published articles and 14% of national production is concentrated in seven researchers. Considering the results recommendations are made, as for example, the search for greater rigor and relevance in the methodological procedures and formation of stable research groups, which would allow the maturation of production, now considered initial.